2018
DOI: 10.1029/2017wr020963
|View full text |Cite
|
Sign up to set email alerts
|

Acidification and Climate Linkages to Increased Dissolved Organic Carbon in High‐Elevation Lakes

Abstract: Increasing concentrations of dissolved organic carbon (DOC) in the northeastern U.S. have been attributed to two potential mechanisms: recovery from acidification and changing climate. Maine's high‐elevation lakes (>600m) could potentially provide unique insight into the response of surface water chemistry to declining acidic deposition and interannual climate variability. The geochemical response in 29 lakes was analyzed during 30 years of change in sulfate ( SO42−) deposition and climate. All 29 lakes exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 86 publications
1
19
0
Order By: Relevance
“…Other characteristics could also mediate the strength of the relationship between climate and water quality; for example, deep waters of small lakes have shown muted responses to warming because of lower physical mixing (Winslow et al, ). Because other variables are known to moderate the effects of climate change on lakes, and the effects of climate are expected to operate in a relatively homogenous way at broad spatial scales (Gavin et al, ; Lapierre et al, ), we hypothesize that the effects of climate will be most clearly expressed in regions with little temporal change in land use and land cover. We were not able to test these hypotheses in the current study, but future work should test these ideas more formally.…”
Section: Discussionmentioning
confidence: 99%
“…Other characteristics could also mediate the strength of the relationship between climate and water quality; for example, deep waters of small lakes have shown muted responses to warming because of lower physical mixing (Winslow et al, ). Because other variables are known to moderate the effects of climate change on lakes, and the effects of climate are expected to operate in a relatively homogenous way at broad spatial scales (Gavin et al, ; Lapierre et al, ), we hypothesize that the effects of climate will be most clearly expressed in regions with little temporal change in land use and land cover. We were not able to test these hypotheses in the current study, but future work should test these ideas more formally.…”
Section: Discussionmentioning
confidence: 99%
“…Despite widespread occurrence of “brownification” of freshwater ecosystems (Gavin et al, ; Hruška et al, ; Monteith et al, ; SanClements et al, ), a growing body of literature has documented that DOC is unchanged or declines over time in many watersheds (Arvola et al, ; Clair et al, ; Raike et al, ; Rodríguez‐Murillo et al, ; Stackpoole et al, 2017), including the northeastern United States (Fahey et al, ; Navrátil et al, ). In the Lamprey River we observed a slight decrease in DOC concentrations over 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, base cation dilution and increases in organic acidity are also influenced indirectly by atmospheric deposition as reflected by soil base cation depletion resulting from enhanced acid leaching and by increases in dissolved organic carbon (DOC) concentrations resulting from declines in the acidity of atmospheric deposition (Gavin et al, 2018;Lawrence et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Responses to decreasing acid deposition may result in changes in the natural and anthropogenic drivers of episodic acidification, but not necessarily to changes in the magnitude of ANC depressions that occur during events (Kline et al, ), though decreases in episodic acidification have also been reported (Riscassi et al, ). Moreover, base cation dilution and increases in organic acidity are also influenced indirectly by atmospheric deposition as reflected by soil base cation depletion resulting from enhanced acid leaching and by increases in dissolved organic carbon (DOC) concentrations resulting from declines in the acidity of atmospheric deposition (Gavin et al, ; Lawrence et al, ).…”
Section: Introductionmentioning
confidence: 99%